Behavior Patterns of Antisocial Teenagers Interacting with Parents and Peers: A Longitudinal Study - Cabrera, Francisco J. P.; Herrera, Ana del Refugio C.; Rubalcava, San J. A.; Martínez, Kalina I. M. (Frontiers in Psychology, 2017)
Antisocial behavior may begin during childhood and if maintained during adolescence, is likely to continue and escalate during adulthood. During adolescence, in particular, it has been established that antisocial behavior may be reinforced and shaped by exchanges between the teenager and his parents and peers, although the molecular process of these relations is as yet unknown. This paper explores the patterns of social interaction established by adolescents with and without the risk of engaging in antisocial behavior in order to understand the exchanges of them with their most important social groups, during two years. The study involved a sample of 70 adolescents classified into these two groups (with risk of antisocial behavior and control group). They were video-recorded interacting with one of their parents and one of their peers, independently. The interaction was done about the negotiation of conflictive conversational topics. Those video-records were registered by pairs of trained observers, using an observational catalog with nineteen behavioral categories, to know about the molecular interactional patterns characteristics. 30 participants were evaluated only once, 30 two times and the other 10 were evaluated three times, the evaluations were performed annually. It was found that a higher occurrence of eye contact and use of open questions and elaborate answers appears to act as a protective factor for engaging in antisocial behavior.